An Unexpected α‐Oxidation of Cyclic Ketones with 1, 4‐Benzoquinone by Enol Catalysis. Issue 33 (28th June 2018) - Shevchenko, Grigory A.; Oppelaar, Barry; List, Benjamin
Abstract: The first direct and asymmetric α‐aryloxylation of cyclic ketones via enol catalysis has been achieved using quinones as the reaction partners. Catalytic amounts of a phosphoric acid promote the exclusive formation of α, α‐disubstituted ketones from the corresponding α‐substituted ketones in good yields and enantioselectivities (up to 96.5:3.5 er). Preliminary mechanistic experiments suggest that this reaction proceeds via a proton‐coupled electron transfer (PCET) followed by radical recombination. Abstract : Branching out : The first direct and asymmetric α‐aryloxylation of α‐branched ketones using quinones as the reaction partner is described. The targeted products could be obtained in good yields and good to excellent enantioselectivities by using phosphoric acids as catalysts. Preliminary mechanistic experiments support a proton‐coupled electron‐transfer (PCET) mechanism.